Welding rod for automatic welding of 2205 duplex stainless steel and preparation method of welding rod

By adding titanium alloy powder, zirconium ferroalloy powder and niobium ferroalloy powder to the welding rod, the Ti, Zr, and Nb element content is adjusted to form stable nitrides and carbides, which solves the problem of degradation of weld performance after welding and achieves good comprehensive performance of welds after high-temperature heat treatment.

CN119681494APending Publication Date: 2025-03-25JIANGSU UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510159138.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

When welding 2205 duplex stainless steel, after high-temperature heat treatment eliminates residual stress, the tensile strength and corrosion resistance of the welds are significantly reduced.

Method used

Flux powder containing titanium alloy powder, zirconium ferroalloy powder and niobium ferroalloy powder are used to form stable nitrides and carbides by reasonably adjusting the content of Ti, Zr, and Nb elements, stabilize the ferrite phase, and inhibit the precipitation of unfavorable phases.

Benefits of technology

It effectively improves the mechanical properties, toughness and corrosion resistance of the weld after high-temperature heat treatment, broadens the heat treatment process window, and improves welding efficiency and process flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005270484940000021
    Figure BDA0005270484940000021
  • Figure BDA0005270484940000041
    Figure BDA0005270484940000041
  • Figure BDA0005270484940000051
    Figure BDA0005270484940000051
Patent Text Reader

Abstract

The invention relates to the technical field of welding rods for automatic welding of 2205 duplex stainless steel, in particular to a welding rod for automatic welding of 2205 duplex stainless steel and a preparation method of the welding rod. When the residual stress at the welding seam of the 2205 duplex stainless steel is eliminated through heat treatment, the tensile strength and the corrosion resistance of the welding seam can be remarkably reduced. In order to solve the technical problems, the welding rod for 2205 duplex stainless steel automatic welding comprises a flux core and a coating, the coating is formed by evenly mixing a binding agent and welding flux powder, and titanium-iron alloy powder, zirconium-iron alloy powder and niobium-iron alloy powder are added into components of the welding flux powder at the same time; according to the method, the contents of Ti, Zr and Nb elements in the electrode coating are increased, so that the purposes of refining grains of a weld joint and stabilizing ferrite are achieved, transformation of ferrite to austenite in the high-temperature heat treatment process of the weld joint is reduced, a proper amount of iron powder is added into the electrode, and the efficiency of automatic welding is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of duplex stainless steel, and in particular to a welding rod for automated welding of 2205 duplex stainless steel and a preparation method thereof. Background Art

[0002] Duplex stainless steel (such as 2205 duplex stainless steel) is widely used in petrochemical, marine engineering, nuclear power and other fields due to its excellent mechanical properties and corrosion resistance.

[0003] The structure of 2205 duplex stainless steel is composed of ferrite (α phase) and austenite (γ phase). Ideally, the ratio of the two phases is close to 1:1. This duplex structure makes it have both high strength and high toughness. However, duplex stainless steel is prone to residual stress during welding, which affects the mechanical properties and corrosion resistance of the weld. Therefore, heat treatment is usually required after welding to eliminate residual stress and improve the comprehensive performance of the weld.

[0004] Although high temperature heat treatment (such as above 650℃) can eliminate residual stress, it will lead to a decrease in the ferrite content in the weld, and the formation of nitrides (such as Cr2N), σ phase and carbides (such as M 23 C6) precipitation, thus significantly reducing the toughness, strength and corrosion resistance of the weld. The existing technology has not effectively solved this problem, resulting in the possibility of early failure or performance degradation of the welded joint in practical applications. Summary of the invention

[0005] The problem in the prior art is that when the residual stress at the weld of 2205 duplex stainless steel is eliminated by heat treatment, the tensile strength and corrosion resistance of the weld will be significantly reduced. In view of the above technical problems, the present invention provides a welding rod for 2205 duplex stainless steel automatic welding, which includes a flux core and a coating, the coating accounts for 35-40% of the total mass of the welding rod, the coating is formed by a uniform mixture of a binder and a flux powder, the mass ratio of the binder to the flux powder is 1:4-5, and the composition of the flux powder is simultaneously added with titanium-iron alloy powder, zirconium-iron alloy powder and niobium-iron alloy powder, the element mass ratio between Ti and Zr and Nb in the titanium-iron alloy powder, zirconium-iron alloy powder and niobium-iron alloy powder is 0.6-1.3:0.2-0.4:0.5-0.6, and the composition of the flux core, in terms of mass percentage, includes the following components:

[0006] C≤0.03%;

[0007] Si≤1%;

[0008] Mn≤2%;

[0009] P≤0.045%;

[0010] S≤0.03%;

[0011] Ni 8-12%;

[0012] Cr 18-20%;

[0013] Fe balance and inevitable impurities.

[0014] Preferably, the core is low carbon stainless steel.

[0015] Preferably, the low carbon stainless steel is 304L stainless steel.

[0016] Preferably, the flux powder comprises the following components in parts by mass:

[0017]

[0018] The mass ratio of Ti to Zr and Nb in the elemental components of the titanium-iron alloy powder, the zirconium-iron alloy powder and the niobium-iron alloy powder is 0.6-1.3:0.2-0.4:0.5-0.6.

[0019] Preferably, the zirconium content in the ferro-zirconium alloy powder is about 30-40%, the Si content is 47-52%, and the balance is Fe and Al.

[0020] Preferably, the grade of the titanium-iron alloy powder in the flux powder is FeTi30 or FeTi40, the titanium content of FeTi30 is about 25-35%, and the titanium content of FeTi40 is about 35-40%.

[0021] Preferably, the grade of the ferroniobium alloy powder in the flux powder is FeNb50 or FeNb60, the niobium content of FeNb60 is about 50-60%, and the niobium content of FeNb50 is about 60-70%.

[0022] Preferably, the average particle size of each component in the flux powder is 20-80 meshes.

[0023] Preferably, the binder is potassium sodium water glass.

[0024] Preferably, the modulus of the potassium-sodium water glass is 2.8-3.1, and the potassium-sodium ratio is 3:1.

[0025] The physical and chemical analysis of each component in the flux powder is as follows:

[0026] Calcium oxide powder: As an alkaline oxide, calcium oxide helps desulfurization and dephosphorization, reduces impurities in the weld and improves the purity of the weld. At the same time, it can stabilize the arc and improve welding process performance.

[0027] Rutile powder: Rutile (TiO2) is a common flux component that can stabilize the arc, improve droplet transfer, reduce spatter, and improve the surface quality of the weld. It can also increase the fluidity of the slag and facilitate slag removal.

[0028] Calcium fluoride powder: Calcium fluoride (CaF2) helps to lower the melting point of the slag, increase the fluidity of the slag, and facilitate slag removal. At the same time, it can also combine with hydrogen to reduce the hydrogen content in the weld and prevent hydrogen-induced cracks.

[0029] Mica powder: Mica powder can improve the insulation performance of the flux, stabilize the arc, and reduce spatter. It can also improve the covering performance of the slag and protect the molten pool from air pollution.

[0030] Magnesium powder: Magnesium powder can be used as a deoxidizer to reduce the oxygen content in the weld and prevent the formation of pores. At the same time, it can also refine the grains and improve the mechanical properties of the weld.

[0031] Marble powder: Marble (CaCO3) decomposes at high temperature to produce CO2, which can protect the molten pool from air pollution. At the same time, it can also provide an alkaline environment, which is conducive to desulfurization and dephosphorization.

[0032] Cryolite powder: Cryolite (Na3AlF6) can lower the melting point of slag, increase the fluidity of slag, and facilitate slag removal. It can also stabilize the arc and reduce spatter.

[0033] Chromium powder: Chromium powder is mainly used to supplement the chromium content in the weld to ensure that the weld has similar corrosion resistance as the base material. Chromium is an important alloying element in duplex stainless steel and can improve the corrosion resistance and strength of the material.

[0034] Ferro-molybdenum alloy powder: Ferro-molybdenum alloy powder is used to supplement the molybdenum content in the weld. Molybdenum can improve the pitting and crevice corrosion resistance of stainless steel, especially in chlorine-containing environments.

[0035] Manganese powder: Manganese powder can be used as a deoxidizer to reduce the oxygen content in the weld and prevent the formation of pores. At the same time, it can also improve the strength and toughness of the weld.

[0036] Iron powder: improves deposition rate, reduces welding layers, and shortens welding time.

[0037] Ferrochromium nitride powder: Ferrochromium nitride powder is used to supplement the nitrogen content in the weld. Nitrogen is an important element in duplex stainless steel, which can improve the strength and corrosion resistance of the material, especially the pitting resistance.

[0038] Ferro-titanium alloy powder: Ferro-titanium alloy powder can act as a stabilizer, combining with carbon to form titanium carbide, preventing the formation of chromium carbide, thereby maintaining the corrosion resistance of the weld. Titanium can also refine the grains and improve the mechanical properties of the weld.

[0039] Zirconium-iron alloy powder: Zirconium and silicon in zirconium-iron alloy powder can act as deoxidizers to reduce the oxygen content in the weld and prevent the formation of pores. Zirconium can also refine the grains and improve the mechanical properties of the weld.

[0040] Niobium-iron alloy powder: Niobium-iron alloy powder can act as a stabilizer, combining with carbon to form niobium carbide, preventing the formation of chromium carbide, thereby maintaining the corrosion resistance of the weld. Niobium can also refine the grains and improve the mechanical properties of the weld.

[0041] The present invention has the following beneficial effects:

[0042] (1) The present invention can refine the grains, improve the stability of ferrite, reduce the transformation of ferrite to austenite during high-temperature heat treatment, and stabilize the ferrite phase, so that the weld still has good mechanical properties, toughness and corrosion resistance after high-temperature heat treatment by increasing the content of Ti, Zr and Nb elements in the welding rod;

[0043] (2) The Ti, Zr, and Nb elements added to the welding rod obtained by the present invention have a strong affinity with nitrogen (N is an essential element for the formation of austenite), and can preferentially form stable nitrides (such as TiN, ZrN, and NbN) with nitrogen, reduce the precipitation of chromium nitride (Cr2N), and prevent the transformation of ferrite to austenite, thereby effectively inhibiting the precipitation of Cr2N, avoiding grain boundary embrittlement and local chromium depletion, and thus improving the toughness and corrosion resistance of the weld;

[0044] (3) The Ti, Zr, and Nb elements added to the welding rod of the present invention can form stable carbides with carbon, thereby effectively inhibiting the formation of σ phase and chromium carbide (M 23 C6), by inhibiting the precipitation of σ phase and carbides, the weld can still maintain good toughness and strength after high temperature heat treatment;

[0045] (4) The present invention reasonably adds and adjusts the contents of Ti, Zr and Nb elements, so that the mass fractions of Ti, Zr and Nb in the flux powder composition are 0.6-1.3:0.2-0.4:0.5-0.6, which significantly improves the structural stability of the weld during high-temperature heat treatment and broadens the heat treatment process window. Even if heat treatment is performed at a higher temperature, the weld can still maintain good comprehensive performance, thereby improving the flexibility and reliability of the process;

[0046] (5) The welding rod obtained by the present invention contains an appropriate amount of iron powder, which improves the deposition rate, reduces the number of welding layers, can effectively shorten the automated welding time, and significantly improves the welding efficiency. DETAILED DESCRIPTION

[0047] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention. Unless otherwise specified, the raw materials in the following examples of the present invention are purchased from outside. The average particle size of each component of the flux powder in the following examples of the present invention is 80 mesh.

[0048] The binder in the following embodiments of the present invention is potassium sodium water glass, with a modulus of 2.8-3.1 and a potassium sodium ratio of 3:1.

[0049] The purity of the chromium powder, ferromolybdenum alloy powder, manganese powder, magnesium powder and iron powder in the following embodiments of the present invention is ≥99.9%.

[0050] In the zirconium-iron alloy powder of the following examples of the present invention, the zirconium content is about 30-40%, the Si content is 47-52%, and the balance is Fe and Al.

[0051] Example 1

[0052] A welding rod for automatic welding of 2205 duplex stainless steel, which consists of a flux core and a coating, wherein the coating accounts for 35% of the total mass of the welding rod, and the coating is formed by uniformly mixing a binder and a flux powder, wherein the mass ratio of the binder to the flux powder is 1:4, and the flux core is 304L stainless steel with a diameter of 3.2 mm. The flux powder, in terms of mass fraction, has the following components:

[0053]

[0054]

[0055] Among the above ingredients, the grade of titanium-iron alloy powder is FeTi30, the grade of niobium-iron alloy powder is FeNb50, the grade of chromium-iron nitride powder is FeNCr3-A, and the grade of molybdenum-iron alloy powder is Fe50Mo.

[0056] The preparation method of the above-mentioned 2205 duplex stainless steel automated welding electrode is as follows:

[0057] (1) uniformly mixing the flux powder and the binder according to the formula amount to obtain a mixed material;

[0058] (2) Compounding the mixture obtained in step (1) with a 304L stainless steel core by a pressure coating device at 10 MPa, so that the core outer surface is evenly coated with the coating.

[0059] Example 2

[0060] A welding rod for automatic welding of 2205 duplex stainless steel, which consists of a flux core and a coating, wherein the coating accounts for 38% of the total mass of the welding rod, and the coating is formed by uniformly mixing a binder and flux powder, wherein the mass ratio of the binder to the flux powder is 1:4, and the flux core is 304L stainless steel with a diameter of 3.2 mm. The flux powder, in terms of mass fraction, has the following components:

[0061]

[0062]

[0063] Among the above ingredients, the grade of titanium-iron alloy powder is FeTi30, the grade of niobium-iron alloy powder is FeNb60, the grade of chromium-iron nitride powder is FeNCr3-A, and the grade of molybdenum-iron alloy powder is Fe50Mo.

[0064] The preparation method of the above-mentioned 2205 duplex stainless steel automated welding electrode is as follows:

[0065] (1) uniformly mixing the flux powder and the binder according to the formula amount to obtain a mixed material;

[0066] (2) Compounding the mixture obtained in step (1) with a 304L stainless steel core by a pressure coating device at 12 MPa, so that the core outer surface is evenly coated with the coating.

[0067] Example 3

[0068] A welding rod for automatic welding of 2205 duplex stainless steel, which consists of a flux core and a coating, wherein the coating accounts for 40% of the total mass of the welding rod, and the coating is formed by uniformly mixing a binder and flux powder, wherein the mass ratio of the binder to the flux powder is 1:4, and the flux core is 304L stainless steel with a diameter of 3.2 mm. The flux powder, in terms of mass fraction, has the following components:

[0069]

[0070]

[0071] Among the above ingredients, the grade of titanium-iron alloy powder is FeTi40, the grade of niobium-iron alloy powder is FeNb50, the grade of chromium-iron nitride powder is FeNCr3-A, and the grade of molybdenum-iron alloy powder is Fe50Mo.

[0072] The preparation method of the above-mentioned 2205 duplex stainless steel automated welding electrode is as follows:

[0073] (1) uniformly mixing the flux powder and the binder according to the formula amount to obtain a mixed material;

[0074] (2) Compounding the mixture obtained in step (1) with a 304L stainless steel core by a pressure coating device at 14 MPa, so that the core outer surface is evenly coated with the coating.

[0075] Example 4

[0076] A welding rod for automatic welding of 2205 duplex stainless steel, which consists of a flux core and a coating, wherein the coating accounts for 36% of the total mass of the welding rod, and the coating is formed by uniformly mixing a binder and a flux powder, wherein the mass ratio of the binder to the flux powder is 1:4, and the flux core is 304L stainless steel with a diameter of 3.2 mm. The flux powder, in terms of mass fraction, has the following components:

[0077]

[0078] Among the above ingredients, the grade of titanium-iron alloy powder is FeTi40, the grade of niobium-iron alloy powder is FeNb60, the grade of chromium-iron nitride powder is FeNCr3-A, and the grade of molybdenum-iron alloy powder is Fe50Mo.

[0079] The preparation method of the above-mentioned 2205 duplex stainless steel automated welding electrode is as follows:

[0080] (1) uniformly mixing the flux powder and the binder according to the formula amount to obtain a mixed material;

[0081] (2) Compounding the mixture obtained in step (1) with a 304L stainless steel core by a pressure coating device at 15 MPa, so that the core outer surface is evenly coated with the coating.

[0082] Example 5

[0083] A welding rod for automatic welding of 2205 duplex stainless steel, which consists of a flux core and a coating, wherein the coating accounts for 35% of the total mass of the welding rod, and the coating is formed by uniformly mixing a binder and flux powder, wherein the mass ratio of the binder to the flux powder is 1:5, and the flux core is 304L stainless steel with a diameter of 3.2 mm, and the flux powder, in terms of mass fraction, has the following components:

[0084]

[0085] Among the above ingredients, the grade of titanium-iron alloy powder is FeTi30, the grade of niobium-iron alloy powder is FeNb60, the grade of chromium-iron nitride powder is FeNCr3-A, and the grade of molybdenum-iron alloy powder is Fe50Mo.

[0086] The preparation method of the above-mentioned 2205 duplex stainless steel automated welding electrode is as follows:

[0087] (1) uniformly mixing the flux powder and the binder according to the formula amount to obtain a mixed material;

[0088] (2) Compounding the mixture obtained in step (1) with a 304L stainless steel core by a pressure coating device at 15 MPa, so that the core outer surface is evenly coated with the coating.

[0089] Comparative Example 1 is the same as Example 1, except that no titanium-iron alloy powder is added in Comparative Example 1.

[0090] Comparative Example 2 is the same as Example 1, except that no zirconium-iron alloy powder is added in Comparative Example 2.

[0091] Comparative Example 3 is the same as Example 1, except that no ferroniobium alloy powder is added in Comparative Example 3.

[0092] Comparative Example 4 is the same as Example 1, except that the mass fraction of the ferrotitanium alloy powder in Comparative Example 4 is 1 part.

[0093] Comparative Example 5 is the same as Example 1, except that the mass fraction of the ferrotitanium alloy powder in Comparative Example 5 is 5 parts.

[0094] Comparative Example 6 is ER2209 duplex stainless steel welding wire, and the welding wire specification is Ф3.2mm.

[0095] Performance Testing

[0096] The welding process conditions are shown in Table 1:

[0097] Table 1

[0098]

[0099] The welding rods obtained in Examples 1-5 of the present invention and Comparative Examples 1-6 were respectively used to weld the UNSS32205 base metal. After welding, the mechanical properties of the cladding metal at the weld were tested. The test results are shown in Table 2:

[0100] Mechanical properties of cladding metal at weld: Tested according to the tensile test method recorded in ASTM E8 / E8M "Tensile Test Methods for Metallic Materials".

[0101] Table 2

[0102] Test items Tensile strength(MPa) Elongation(%) Example 1 850 27.5 Example 2 855 27.0 Example 3 848 27.8 Example 4 853 27.3 Example 5 851 27.6 Comparative Example 1 833 29.2 Comparative Example 2 824 30.1 Comparative Example 3 830 29.3 Comparative Example 4 832 29.2 Comparative Example 5 838 28.8 Comparative Example 6 830 29.0

[0103] Then, the welds obtained in Examples 1-5 and Comparative Examples 1-6 were heat treated, and the heat treatment process was as follows:

[0104] (1) Place the welding sample in an annealing furnace and heat it from room temperature to 350°C for 1 hour;

[0105] (2) The welding sample is then heated from 350°C to 690°C for 1.5 hours;

[0106] (3) Keep the welded specimen at 690°C for 1 h.

[0107] (4) Turn off the power of the annealing furnace, open the furnace door, and let the welded sample cool naturally to room temperature. Then, the mechanical properties of the cladding metal at the weld were tested. The test results are shown in Table 3:

[0108] Table 3

[0109] Test items Tensile strength(MPa) Elongation(%) Example 1 830 29.1 Example 2 835 28.5 Example 3 828 29.3 Example 4 833 28.8 Example 5 831 29.1 Comparative Example 1 783 33.7 Comparative Example 2 774 34.6 Comparative Example 3 780 33.8 Comparative Example 4 782 33.7 Comparative Example 5 788 33.3 Comparative Example 6 763 35.0

[0110] Intergranular corrosion tests were carried out on the welds after heat treatment, specifically in accordance with the standard GB / T4334.5-2020 "Stainless Steel Corrosion Test Method Part 5: Sulfuric Acid-Copper Sulfate Corrosion Test". The corrosion time was 16 hours. After the test, the sample was taken out and cleaned, and the surface of the sample was observed with a low-power magnifying glass. The test results showed that the welds formed in Examples 1-5 had no cracks on the surface after the intergranular corrosion test, indicating that the welds had strong resistance to intergranular corrosion. There were no cracks on the surfaces of the welds obtained in Comparative Examples 2-3, respectively, while microcracks appeared on the surfaces of the welds obtained in Comparative Examples 1 and Comparative Examples 4-6, respectively.

[0111] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A welding rod for automated welding of 2205 duplex stainless steel, characterized in that: The invention comprises a flux core and a flux coating, wherein the flux coating accounts for 35-40% of the total mass of the electrode, the flux coating is formed by uniformly mixing a binder and a flux powder, the mass ratio of the binder to the flux powder is 1:4-5, the flux powder is simultaneously added with titanium-iron alloy powder, zirconium-iron alloy powder and niobium-iron alloy powder, the mass ratio of Ti to Zr and Nb in the titanium-iron alloy powder, zirconium-iron alloy powder and niobium-iron alloy powder is 0.6-1.3:0.2-0.4:0.5-0.6, and the composition of the flux core, in terms of mass percentage, comprises the following components: C≤0.03%; Si≤1%; Mn≤2%; P≤0.045%; S≤0.03%; Ni 8-12%; Cr 18-20%; Fe balance and inevitable impurities.

2. A 2205 duplex stainless steel automated welding electrode according to claim 1, characterized in that: The core is made of low carbon stainless steel.

3. A 2205 duplex stainless steel automated welding electrode according to claim 2, characterized in that: The low carbon stainless steel is 304L stainless steel.

4. The 2205 duplex stainless steel automated welding electrode according to claim 1, characterized in that: The flux powder comprises the following components in parts by mass: 5-10 parts of calcium oxide powder; 15-20 parts of rutile powder; Calcium fluoride powder 10-15 parts; 3-5 parts of mica powder; 0.5-2 parts of magnesium powder; 8-15 parts of marble powder; 5-10 parts of cryolite powder; 20-28 parts of chromium powder; 8-12 parts of ferromolybdenum alloy powder; 1-5 parts of manganese powder; 1-3 parts of iron powder; 1-2 parts of ferrochrome nitride powder; 3-9 parts of ferrotitanium alloy powder; 1-3 parts of ferrozirconium alloy powder; 1-3 parts of ferroniobium alloy powder; Among the above components, the mass ratio of Ti to Zr and Nb in the elemental components of the titanium-iron alloy powder, the zirconium-iron alloy powder and the niobium-iron alloy powder is 0.6-1.3:0.2-0.4:0.5-0.

6.

5. A welding rod for automatic welding of 2205 duplex stainless steel according to claim 4, characterized in that: The zirconium content in the ferro-zirconium alloy powder of the flux powder is about 30-40%, the Si content is 47-52%, and the balance is Fe and Al.

6. A 2205 duplex stainless steel automated welding electrode according to claim 4, characterized in that: The grade of the titanium-iron alloy powder in the flux powder is FeTi30 or FeTi40.

7. A welding rod for automatic welding of 2205 duplex stainless steel according to claim 4, characterized in that: The grade of ferroniobium alloy powder in the flux powder is FeNb50 or FeNb60.

8. The 2205 duplex stainless steel automated welding electrode according to claim 1, characterized in that: The average particle size of each component in the flux powder is 20-80 meshes.

9. The 2205 duplex stainless steel automated welding electrode according to claim 1, characterized in that: The binder is potassium sodium water glass.

10. A welding rod for automatic welding of 2205 duplex stainless steel according to claim 9, characterized in that: The modulus of the potassium-sodium water glass is 2.8-3.1, and the potassium-sodium ratio is 3:1.

Citation Information

Cited By

  • High-nitrogen high-elongation stainless steel flux-cored wire and preparation method thereof

    CN120347423A

  • High nitrogen and high elongation stainless steel flux-cored wire and method of making same

    CN120347423B